Textual Analysis of Corruption News Text on Trans TV and Global TV Media: Critical Discourse Analysis by Norman Fairclough (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study is to describe the textual level of discourse on reporting corruption in Trans TV and Global TV media. The research employed a theoretical and methodological approach. Theoretically, this research used a model of critical discourse analysis by Norman Fairclough. The methodological approach used in this research was descriptive qualitative. The results of the study were concerned with two things. Firstly, the vocabulary used in the E-KTP corruption news texts broadcasted on Trans TV tend to be in the form of a formal vocabulary, while those on Global TV tend to use informal vocabulary. The expressions used in Trans TV tend to be the expression of euphemism, while those on Global TV tend to use metaphors. Secondly, regarding grammatical analysis, Trans TV and Global TV utilize active and passive sentences, positive-negative sentences, modalities, and personal pronouns. Thirdly, regarding text structure analysis, the corruption news texts on Trans TV and Global TV tend to show a pattern or structure consisting of five elements, namely the news headline, news date, news lead, news body, and the end of the news.